Prenatal Diagnosis and Management of a Fetus with Double Aortic Arch: A Case Report and Literature Review - Alireza Golbabaei; Mahsa Naemi; Maasoumeh saleh (International Journal of Cardiovascular Practice)
Double aortic arch is a congenital vascular abnormality in which the connected segments and their branches course between and compress the trachea and esophagus, often resulting in invariable airway compression and gastrointestinal presentations. A 2-month girl with a history of double aortic arch diagnosis in fetal echocardiography was admitted to our hospital with recurrent pneumonia. The double aortic arch was confirmed by computed tomography angiogram. After surgery, the patient was followed for one year of age and had no problem. Our study showed early diagnosis and treatment of a double aortic arch might prevent chronic, irreversible complications.